Determinants of the Energy Development Based on Renewable Energy Sources in Poland - Jan L. Bednarczyk; Katarzyna Brzozowska-Rup; Sławomir Luściński (Energies, 2021)
In this article, we aim to identify the determinants that profoundly impact renewable energy sources development in Poland. To this end, the authors have conducted qualitative and quantitative analyses of Poland’s renewable energy sector. In this paper, we demonstrate an original approach considering the different development levels of the given sector across provinces (voivodeships). It uses panel data from the Local Data Bank of the Statistics Poland on electricity production from renewable energy sources in individual voivodeships in Poland from 2005 through 2019. The study confronts the results of previous studies and sheds light on the situation in Poland—specifically, upon the changes that have happened over the ten years (2010–2019). The qualitative analysis shows a negative correlation between energy consumption and the share of renewable energy sources in total energy production. Evidence shows that favorable changes are underway in the energy production structure: RES share is growing and by degrees satisfying energy demand, and there is growing potential of energy entities in Poland. Furthermore, the analysis shows that R&D and total expenditures on environmental protection and water management investments do not significantly affect the development of RES. A dynamic panel data model has been used to analyze the group and time effects on the dependent variable. The findings confirm the existence of the persistency effect and indicate positive effects of total installed electric capacity (IEC) and household electricity consumption (HEC). Nonhousehold electricity consumption (NHEC) has a negative effect on the endogenous variable, i.e., the renewable energy sources share in the gross final energy consumption (RESS). The research results may be applicable as recommendations for energy efficiency policy development based on renewable energy sources depending on the RES development level in the regions of Poland.